Ambient PM2.5 and Stroke: Effect Modifiers and Population Attributable Risk in Six Low- and Middle-Income Countries. Issue 5 (May 2017) - Lin, Hualiang; Guo, Yanfei; Di, Qian; Zheng, Yang; Kowal, Paul; Xiao, Jianpeng; Liu, Tao; Li, Xing; Zeng, Weilin; Howard, Steven W.; Nelson, Erik J.; Qian, Zhengmin; et al.
Abstract : Background and Purpose—: Short-term exposure to ambient fine particulate pollution (PM2.5 ) has been linked to increased stroke. Few studies, however, have examined the effects of long-term exposure. Methods—: A total of 45 625 participants were interviewed and included in this study, the participants came from the Study on Global Ageing and Adult Health, a prospective cohort in 6 low- and middle-income countries. Ambient PM2.5 levels were estimated for participants' communities using satellite data. A multilevel logistic regression model was used to examine the association between long-term PM2.5 exposure and stroke. Potential effect modification by physical activity and consumption of fruit and vegetables was assessed. Results—: The odds of stroke were 1.13 (95% confidence interval, 1.04–1.22) for each 10 μg/m 3 increase in PM2.5 . This effect remained after adjustment for confounding factors including age, sex, smoking, and indoor air pollution (adjusted odds ratio=1.12; 95% confidence interval, 1.04–1.21). Further stratified analyses suggested that participants with higher levels of physical activity had greater odds of stroke, whereas those with higher consumption of fruit and vegetables had lower odds of stroke. These effects remained robust in sensitivity analyses. We further estimated that 6.55% (95% confidence interval, 1.97%–12.01%) of the stroke cases could be attributable to ambient PM2.5 in the study population. Conclusions—: This study suggests that ambient PM2.5 may increase the risk of stroke and may be responsible for the astounding stroke burden in low- and middle-income countries. In addition, greater physical activity may enhance, whereas greater consumption of fruit and vegetables may mitigate the effect. Abstract : Supplemental Digital Content is available in the text.